Linguagem e sociedade: análise do discurso de cartas de detentas e ex-detentas - Savenhago, Igor José Siquieri (Universidade Federal de São Carlos, 2009)
This work analyzes, discursively, letters from women inserted into the penitentiary system in the region of Ribeirão Preto, brightening the regions of power, the knowledge and learning manifested there, discovering forms of resistance which emerge before the systems of domination. It is rare to hear about the routine, the everyday of these instituitions. When there are rebellions, we can notice a great interest from the press in this theme, but generally, the exposure of the subjects related to the prisons do not proceed to other spheres. Hardly ever does it get to the scientific field. This study, intends to do justly the less explored path: bringing under the eyes of the researcher, a discussion about the prisons for the university. And in which way? By means of analysis of the letters written by the prisoner women and exprisoners from the Female Penitentiary of Ribeirão Preto, between March 2004 and the beginning of 2007, characterizing the voice of these women like a scientific document. So, this research supports, particularly, in theoretical of the analysis of the speech, like Michel Foucault and his understanding on Science and Knowing , Michel Pêcheux and his comprehension on subject and Jacques Le Goff, concerning his writings on document . Thus, we hope to contribute for the constitution in different ways about the manifestation from the learning resulted from the prison system, through the analysis written by the prisoner women and ex-prisoners. And to be cautious are possibilities, particularly, the voice of the prisoners worthy of study in the scientific field, considering the studies of the languages, and not only from those who detain the mechanisms of control from the speeches in the penitentiary system.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Análise do discurso; Sujeito; Cartas; Prisão - controle social; CIENCIAS SOCIAIS APLICADAS